PENINGKATAN MENULIS TEKS DESKRIPSI DENGAN MENGGUNAKAN FILM PADA KELAS 7.10 SMP NEGERI 3 KOTA TANGERANG SELATAN - Ahmad Fadly (Lembaga Penelitian dan Pengabdian Masyarakat Universitas Pancasakti Tegal, 2020)
This research was proposed to increase the ability of descriptive text writing on grade 7 through film media. Film Jembatan Pensil directed by Hasto Broto was implemented in this classroom action research. Though two cycles, this research could increase the ability of descriptive text writing on grade 7 students in SMP Negeri 3 Kota Tangerang Selatan. On the first cycle, the average score obtained is 68.04, while on the second one was obtained 82. It is concluded that film media could increase the ability of descriptive text effectively.